Synthesis of 3-aryl-7-Hydroxy Isochromenes - Prasad Matho, Ram; Ghosh, P.K.; Sarkhel, B.K. (Asian Journal of Chemistry, 2010)
Phenol, anisole and resorcinol have been condensed with 4-hydroxyl homophthalic acid in the presence of polyphosphoric acid to give 3-(4´-hydroxy phenyl)-; 3-( 4´-methoxyphenyl) and 3-(2´,4´ -dihydroxyphenyl)- 7-hydroxy isocoumarins. On treatment with aqueous sodium hydroxide, 3-aryl isocoumarin yield the respective ω-(2´-carboxyl- 4´-hydroxyphenyl)-acetophenones. Sodium boro-hydride reduction of acetophenones gives the corresponding dihydroisocoumarins. The isocoumarins have been condensed with methyl magnesium iodide, ethyl magnesium iodide and phenyl magnesium iodide to yield 3-(4´-hydroxy phenyl), 3-(4´-methoxy phenyl)-, 3-(2´,4´-dihydroxy phenyl)-7-hydroxy-1, 1-dimethyl; 3-(4´-hydroxy phenyl)-, 3-(4´-methoxy phenyl)-3-(2´,4´dihydroxy phenyl)-7-hydroxy-1,1-diethyl and 3-(4´-hydroxy phenyl)-, 3-(4´-methoxy phenyl) and 3-(2´,4´-dihydroxy phenyl)-7-hydroxy-1,1-diphenyl ischromenes. The isocoumarins have been converted into iso- quinolones with ammonia, ethyl amine and aniline.